PENGARUH FAKTOR INTERNAL TERHADAP PENYALURAN KREDIT DENGAN SUKU BUNGA SEBAGAI VARIABEL MODERATING - Kusumawati, Ratih; Manda, Gusganda Suria (Buletin Studi Ekonomi; VOL.26.NO.2.AGUSTUS 2021DO - 10.24843/BSE.2021.v26.i02.p04, 2021)
The purpose of this study was to determine and analyze the influence of internal factors on credit distribution with interest rates as a moderating variable. This research uses quantitative research methods on the population of conventional commercial banks listed on the Indonesia Stock Exchange for the period 2015-2020. Sampling was done by purposive sampling. The analysis technique used is Moderated Regression Analysis. Based on the results of the partial analysis, it is known that the DPK variable has a positive and significant effect on credit distribution. The CAR variable has no effect on credit distribution. And the NPL variable has a negative and significant effect on credit distribution. Meanwhile, the simultaneous analysis shows that there is an influence between DPK, CAR and NPL on credit distribution. The MRA test results show that the interest rate as a moderating variable can strengthen the relationship between DPK and credit distribution, interest rate can strengthen the relationship between CAR and credit distribution, as well as interest rate can weaken the relationship between NPL and credit distribution.